The behavior of tillage tools with acute and obtuse lift angles - Abbaspour-Fard, Mohammad Hossein; Hoseini, Sayed Ali; Aghkhani, Mohammad Hossein; Sharifi, Ahmad (Spanish Journal of Agricultural Research, 2014)
An experimental investigation was conducted to study the trend of draft force against forward speed and working depth for a range of lift angles beyond acute angles for a simple plane tillage tool. The experiments were performed in an indoor soil bin facility equipped with a tool carriage and a soil preparation unit propelled by an integrated hydraulic power system. The system was also equipped with electronic instrumentation including an Extended Octagonal Ring Transducer (EORT) and a data logger. The factorial experiment (4×3×3) with three replications was used based on Randomized Complete Block Design (RCBD). The independent variables were lift angle of the blade (45, 70, 90 and 120°), forward speed (2, 4 and 6 km h-1) and working depth (10, 25 and 40 cm). The variance analysis for the draft force shows that all independent variables affect the draft force at 1% level of significance. The trend of the draft force against working depth and forward speed had almost a linear increase. However, the trend of the draft force against the lift angle is reversed for lift angles >90. This finding, conflicts with the results of analytical and numerical studies which extrapolate the results achieved for acute lift angles to obtuse lift angles and have not been reported experimentally.